Simulation Analysis and Experimental Verification of Dynamic and Thermal Stability Characteristics of 500kV High Coupling Split Reactor. Issue 4 (January 2021) - Liu, Junxiang; Meng, Qingmin; Zhang, Xiancong; Luo, Junting; Wang, Lizhong; Feng, Jiaqi
Abstract: This paper introduces the basic principle of 500kV high coupling split reactor, and the simulation analysis of leakage magnetic field, temperature field and winding electromagnetic force of maneuvering thermal stability characteristics. The feasibility of the design scheme is verified by the equivalence test of mechanical strength of small prototype.